2011
DOI: 10.1371/journal.pone.0025418
|View full text |Cite
|
Sign up to set email alerts
|

An α/β Hydrolase and Associated Per-ARNT-Sim Domain Comprise a Bipartite Sensing Module Coupled with Diverse Output Domains

Abstract: The RsbQ α/β hydrolase and RsbP serine phosphatase form a signaling pair required to activate the general stress factor σB of Bacillus subtilis in response to energy limitation. RsbP has a predicted N-terminal Per-ARNT-Sim (PAS) domain, a central coiled-coil, and a C-terminal protein phosphatase M (PPM) domain. Previous studies support a model in which RsbQ provides an activity needed for PAS to regulate the phosphatase domain via the coiled-coil. RsbQ and the PAS domain (RsbP-PAS) therefore appear to form a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…The essentiality of CD2684 in both the wild‐type strain and the sigB mutant support the idea that this oxidoreductase might be involved in the production of a metabolite crucial for C. difficile . As proposed for the PAS domain of RsbP in B. subtilis (Nadezhdin et al, ), this compound could be detected by the GAF domain located in the N‐terminal part of RsbZ modulating its phosphatase activity (Fig. ).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The essentiality of CD2684 in both the wild‐type strain and the sigB mutant support the idea that this oxidoreductase might be involved in the production of a metabolite crucial for C. difficile . As proposed for the PAS domain of RsbP in B. subtilis (Nadezhdin et al, ), this compound could be detected by the GAF domain located in the N‐terminal part of RsbZ modulating its phosphatase activity (Fig. ).…”
Section: Discussionmentioning
confidence: 79%
“…RsbQ interacts with the PAS domain of RsbP and is required for a proper σ B activity (Brody et al, ). In addition, it has been proposed that an unidentified metabolite produced by RsbQ leads to σ B activation through the RsbP PAS domain (Nadezhdin et al, ). Contrary to RsbP and RsbQ, CD2684 and RsbZ do not seem to interact with each other as suggested by our experiment using the BACTH system (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the crystal structure of RsbQ, which shows the putative active site buried in a small, hydrophobic cavity that is poorly solvent‐accessible, the latter scenario seems more likely . Interestingly, results of yeast‐two‐hybrid assays suggest that RsbP and RsbQ directly interact . The crystal structure somewhat supports the idea of a direct protein–protein interaction between them because RsbQ has a loop region that is distinct from, and unique amongst, other proteins with a similar fold .…”
Section: Rsbp‐mediated Red‐light Activation Of the Energy‐branch Of Tmentioning
confidence: 83%
“…Ultra‐high resolution live‐cell microscopy studies, using both diffraction‐limited microscopy and the super‐resolution technique of PALM, may reveal the dynamical changes in position and mobility of the various Rsb components of the cell, via tagging with a suitable fluorescent reporter . Both the RsbP/Q and the RsbR/S/T modules are well conserved in the Domain of the Bacteria. Thus, computational simulations of their functioning may teach us a lot about similar, related processes in other bacteria like in Firmicutes, Actinobacteria, Proteobacteria and Cyanobacteria . Their genomic context in these organisms suggests that they are likely coupled to a variety of output functions, like, e.g .…”
Section: Discussionmentioning
confidence: 99%
“…Energy stress affects the RsbQ-RsbP signaling pathway sensing glucose, oxygen, and phosphate starvation and the exposure to agents such as NO, azide, and mycophenolic acid (Hecker et al 2007). It has been suggested that the RsbQ α/β hydrolase provides a small molecule, which activates the phosphatase RsbP (Nadezhdin et al 2011).…”
Section: The Sigb Regulonmentioning
confidence: 99%